Ens, verum, bonum, universales en Tomás de Aquino - Trujillo Werner, Augusto (2017)
This scholarship article explains how Aquinas understood: (1) The abstraction of the ens, verum et bonum simpliciter. (2) The establishment of the first and second practical commandments in a person. (3) The practical imperative “do good (universal and particularhuman) and avoid (universal and particularhuman) evil”.